Vending Machine for Enhancing Healthcare Access - Satheesh Anantha Rao; Yee See Khee (Emerging Advances in Integrated Technology, 2025)
This project addresses challenges in pharmacy access and feedback mechanisms for vending machine utilization by developing an advanced healthcare vending system. The system integrates RFID technology and an Arduino Mega microcontroller to enable secure dispensing and a conceptual RFID-based payment system. Additionally, an MIT App was developed to provide customer assistance. The methodology involved designing and assembling the vending machine’s mechanical and electrical components, programming the Arduino Mega, and testing the system. Results demonstrated robust RFID tag detection at 100% within 1.0 cm, declining accuracy at greater distances, and product vending accuracy ranging from 70% to 90% across slots. These findings highlight the potential of the system to enhance healthcare accessibility through reliable dispensing technology. Future improvements include IoT-based real-time inventory tracking for stock and expiration monitoring and implementing a Telegram bot for intelligent inventory management.